FIELD STRENGTHS OF SOME VLF TRANSMISSIONS AND ATMOSPHERIC NOISE MEASURED IN ASIA, JUNE 1963 THROUGH MARCH 1964 - Garner, W. E.; Rhoads, F. J.; Schauer, R. L. (1965)
The Naval Research Laboratory is conducting an investigation of very- low-frequency (VLF) radio wave propagation at great distances and over a long period of time. The statistical relationship of the field strength of various VLF transmissions and atmospheric noise and the signal-to-noise ratios with the time of day and season of the year is being investigated. Between December 1958 and March 1964 the subject propagation data was recorded at the following sites: Hammerfest, Bode and Varhaug, Norway; Rome, Italy; Haifa, Israel; and Karachi, West Pakistan.